Investigating Indonesian Learners’ Use of The Mother Tongue (L1) In English for Specific Purposes Classrooms: A Survey-Based Study - Bunga Putri Maulia; Abdullah Kafabih (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study investigates learners’ use of the mother tongue in English for Specific Purposes classrooms and examines students’ perceptions of lecturers’ use of the mother tongue as part of instructional practice. Drawing on a descriptive survey design, data were collected from 66 students enrolled in ESP courses at a public university in Indonesia. The participants, drawn from several intact classes, completed an online questionnaire adapted from an established instrument and contextualized to the Indonesian setting. The questionnaire explored the frequency and functions of students’ mother tongue use as well as their evaluations of teachers’ use of the mother tongue in explaining vocabulary, grammar, instructions, and discipline related content. The data were analyzed using descriptive statistics, including means, standard deviations, frequencies, and percentages. The findings indicate that learners do not rely on their first language indiscriminately but use it selectively to support comprehension, peer collaboration, and expressive clarity in cognitively demanding situations. In addition, students perceive lecturers’ use of the mother tongue as pedagogically appropriate when it serves specific instructional purposes, particularly in clarifying technical terminology and complex professional concepts. English remains recognized as the primary medium of instruction, while the mother tongue functions as a supportive resource. These findings provide empirical support for a balanced and context sensitive approach to mother tongue use in ESP instruction and contribute to ongoing discussions on multilingual practices in higher education. The study is limited by the use of convenience sampling, the relatively small sample size, and reliance on self-reported questionnaire data, which may affect the generalizability of the results.